2019
DOI: 10.1111/hepr.13321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological features of sarcopenia‐related indices in patients with non‐alcoholic fatty liver disease

Abstract: Background Sarcopenia is diagnosed with the skeletal muscle index (SMI) or the sarcopenia index (SI). We previously reported that the ratio of skeletal muscle mass to body fat mass (SF ratio) was a novel index of sarcopenia in patients with non‐alcoholic fatty liver disease (NAFLD). The aim of this retrospective study was to evaluate sarcopenia with these indices in patients with NAFLD. Methods One hundred and fifty‐six consecutive patients with biopsy‐proven NAFLD and alanine aminotransferase (ALT) >40 IU/L w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…CC is used to mainly evaluate muscle mass (correlation coefficient of our data between CC and SMI was: r=0.79 in males and r=0.83 in females) and BMI is used to mainly evaluate fat mass. BMI can be critical for assessing sarcopenia in CLDs, while caution should be exercised for the presence of sarcopenic obese patients (40). In this study, of the 175 male patients with visceral obesity (WC ≥85 cm), 10 (5.71%) had sarcopenia, while of the 91 female patients with visceral obesity (WC ≥90 cm), 5 (5.49%) had sarcopenia.…”
Section: Discussionmentioning
confidence: 76%
“…CC is used to mainly evaluate muscle mass (correlation coefficient of our data between CC and SMI was: r=0.79 in males and r=0.83 in females) and BMI is used to mainly evaluate fat mass. BMI can be critical for assessing sarcopenia in CLDs, while caution should be exercised for the presence of sarcopenic obese patients (40). In this study, of the 175 male patients with visceral obesity (WC ≥85 cm), 10 (5.71%) had sarcopenia, while of the 91 female patients with visceral obesity (WC ≥90 cm), 5 (5.49%) had sarcopenia.…”
Section: Discussionmentioning
confidence: 76%
“…However, to investigate the association between decreased muscle mass and the risk of NAFLD, several studies have used a SMI that is calculated as the skeletal muscle mass divided by bodyweight; that is, a weight-adjusted SMI (%). [20][21][22][23][24][25] A weight-adjusted SMI might decline when the bodyweight increases due to the increase in fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Several research groups have reported an association between NAFLD and decreased the skeletal muscle mass analyzed using the weight-adjusted skeletal muscle mass index (SMI). [20][21][22][23][24][25] Therefore, the evaluation of only serum creatinine, which reflects the skeletal muscle mass, might be inaccurate for the prediction of NAFLD. We thus hypothesized that serum creatinine divided by bodyweight can reflect the proportion of skeletal muscle mass in the body mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, muscle mass (MM) has also gained prominence in several diseases, including NAFLD 3 . It seems that the connection between the liver, adipose tissue, and muscle occurs through the expression of insulin receptors in these tissues, in view of the anabolic role of insulin, in the presence of IR in myocytes, protein catabolism increases, resulting in MM depletion and, consequently, in sarcopenia 4 .…”
Section: Introductionmentioning
confidence: 99%